Roost site use by Great (Buceros bicornis) and Wreathed (Rhyticeros undulatus) Hornbill and its implications for seed dispersal. (15th November 2021) - Naniwadekar, Rohit; Rathore, Akanksha; Shukla, Ushma; Datta, Aparajita
Abstract: We examined roost selection by hornbills using telemetry data and determined its implication for seed dispersal. Roost selection was not influenced by nest/foraging sites. Wreathed Hornbill roosts were mostly close to the river. Hornbills dispersed only 10% of seeds at roosts, but dispersal distances of those seeds were longer. Abstract : We examined roost selection by hornbills using telemetric data and determined its implication for seed dispersal. Roost selection was not influenced by nest/foraging sites. Wreathed Hornbill roosts were mostly close to the river. Hornbills dispersed only 10% of seeds at roosts, but dispersal distances of those seeds were longer.